The impact of social psychonalytical study of intergroup communication of Stephen Dedalus in "A portrait of the artist as a young man" and the lacanian theory - Kamarzadeh, Sepideh (Revista Hipótese, 2016)
James Joyce, a remarkable poet, novelist, and writer of avant-garde, was born in 1882 in Ireland, Dublin. From his childhood, he suffers from identity-crisis and from his young hood, he began to write. While he suffers from mocking of others, he writes “A Portrait of the Artist as a Young Man” and it considers as an autobiographical writing. So whatever happens in this novel is regarded as a story of Joyce's own life. James Joyce tolerated a lot of suffering in his lifelong, which most of them composed in this novel. Psychoanalytical study considers most of the psychological view on the human being, which most of its theory is composed by Sigmund Freud, the well-known psychologist, and Jacque Lacan who was a rewriter of Freud's theory and attitude in other way. In this study attempted is made to survey the whole of the story, especially its main character, Stephen Dedalus, by psychoanalytic viewpoints.